Algebraic and Differential Methods for Nonlinear Control Theory : Elements of Commutative Algebra and Algebraic Geometry /: Elements of Commutative Algebra and Algebraic Geometry. ([2019]) - Martínez-Guerra, Rafael; Martínez-Fuentes, Oscar; Montesinos-García, Juan Javier
No abstract available